Acellular matrix hydrogel for repair of the temporomandibular joint disc. Issue 7 (29th June 2020) - Liang, Jiadi; Yi, Ping; Wang, Xiaojin; Huang, Futing; Luan, Xianghong; Zhao, Zuodong; Liu, Chang
Abstract: Application of tissue‐derived extracellular matrix (ECM) biomaterials in the repair of the temporomandibular joint (TMJ) disc is a promising approach for the treatment of disc abrasion and perforation, particularly for the young patient population. Although decellularized ECM (dECM) scaffolds preserve tissue‐specific structures as well as biological and biomechanical properties, they require surgical implantation. To address this issue, we prepared porcine TMJ discs into decellularized ECM with serial detergent and enzyme treatments, and the TMJ disc‐derived ECM was then processed into hydrogels via pepsin digestion. The decellularization efficiency was assessed by quantification of the DNA and matrix component contents. The fibrous ultrastructure of the hydrogel was observed by scanning electron microscopy (SEM). Rheological characterization and mechanical properties were measured. in vitro experiments with costal chondrocytes ensured the cellular proliferative capacity and compatibility in the injectable disc‐derived ECM hydrogel. The results showed that a large amount of DNA (>95%) was removed after decellularization; but, the collagen was retained. SEM of the hydrogels demonstrated a multiaperture fiber ultrastructure. Rheological studies revealed a rapid gelation temperature (37°C) and injectable properties. The mechanical properties of the hydrogels were adjusted by changing the ECM concentration. The in vitro studies revealed that the hydrogels are not cytotoxic, but instead showed good cytocompatibility. The hydrogel also showed good injectability and degradability through an in vivo study. Overall, these results suggest the great potential of injectable disc‐derived hydrogels for TMJ disc repair and regeneration applications.